THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER CONFIDENCE THROUGH CUSTOMER SATISFACTION AS A MEDIATION VARIABLE AT AQIQOHKITA - Sholihah, Rifatus; Kaihatu, Thomas Stefanus (Universitas Ciputra Surabaya, 2024)
This research aims to find out the effect of service quality on customer trust through customer satisfaction with Aqiqahkita as the research object. The variables used in this research are service quality as the independent variable, customer satisfaction as the mediating variable and customer trust as the dependent variable. The method used is quantitative mediation. The sample used in this research used a non-probability sampling method with a purposive sampling technique and the sample consisted of 110 respondents. The data collection technique in this research was carried out by distributing questionnaires using a Likert scale. The results of the analysis concluded that service quality has an influence on customer trust. Service quality also has an influence on customer satisfaction. Customer satisfaction has an influence on customer trust. There is partial mediation of service quality on customer trust through customer satisfaction.